Effects of excessive weather on the micro-climate of apple plantations under the hail protection nets - Lakatos, L.; Gonda, I.; Soltész, M.; Szabó, Z.; Szél, J.; Nyéki, J. (International Journal of Horticultural Science, 2011)
The general utilisation of hail nets is spreading all over the world and in Hungary too. Hail nets are at present the only tool, whichis able to prevent heavy hail damage in agricultural crops. Besides its numerous advantages, there are also deleterious side effects, e.g. itchanges the microclimate of the crop stand. Our study aimed to observe the differences, which characterise the physical status of crop standsunder the protection of hail nets compared with the stands in open air under various meteorological conditions: high or low temperature, calmor windy atmosphere and their possible combinations. The results indicated that on hot and calm days the difference may attain 3–4° C. Oncool summer days, the difference was only 1.5 ºC. The hail net influences the relative humidity of the air, which means on ho summer daysoften 7-8% differences. Conditions of radiation may also differ conspicuously. Measurements prove the reduced global radiation on sunnysummer days to 70%. This impairs as a rule the development of fruits reducing their quality and also its quantitative traits. Sunburn is, on theother hand, significantly prevented by shadow.